Atuação docente na sala de recursos multifuncionais da rede municipal de Macapá/AP - Alves, Helen Cristiane Viana (Universidade Federal de São Carlos, 2018)
The Specialized Educational Assistance is a right established in the Federal Constitution to all students with disabilities, being offered in the Multifunctional Resource Rooms that provide access to services and pedagogical resources and accessibility in schools of the regular network of education. To do so, it is necessary for the schools to provide adequate space for their installation, as well as a specialized teacher for ESA. The present study had as general objective to characterize the teaching performance in multifunctional resource rooms (SRM) of schools of the municipal teaching network of Macapá. Specific objectives were: a) to identify the public that receives specialized educational services in SRMs; b) know the operating conditions and referrals of students to SRMs; c) identify how the teacher organizes his / her teaching work, and d) verify what the teachers think about the school inclusion and implications in the teaching performance. It consisted of a research of qualitative character with exploratory-descriptive character and was realized in Schools of the municipal public network of education in Macapá; having as participants, six (6) teachers who worked in the Specialized Educational Assistance. The schools where the teachers interviewed worked were located in different areas of the city of Macapá, distributed between the North, South, East and West zones, totaling two (2) schools in the South zone, two (2) in the North zone, one ) in the West zone and one (1) in the East zone. The data collection was done through the application of an interview to the teachers who were selected through a lottery. The analyzed data were organized in thematic axes based on the information obtained in the interviews. The results revealed that ESA teachers have a positive conception about inclusion. It was found that a part of multifunctional resource rooms does not have all the necessary resources to attend students, and when they have resources such as games, equipment and computers, they do not work. Students are referred to the specialized educational service by the school secretary and in some situations, the Municipal Education Department, through the Special Education Division, conducts this referral. Participants indicated that the planning of student attendance is done, mostly in partnership with teachers in the regular classroom. As a result, it was also observed that teachers attend a very diversified clientele, which requires adequate training that addresses the demands demanded by the process of school inclusion and that foster student learning, which requires a proposal from the public sector training for these professionals. The data showed the importance of the support of families, the bodies responsible for special education and the school as a whole. It is hoped that this research can contribute with the scientific knowledge and that encourages future works that come to discuss about the Special Education in the municipality of Macapá

El Servicio Educativo Especializado es un derecho establecido en la Constitución Federal a todos los alumnos con discapacidades, siendo ofrecido en las Salas de Recursos Multifuncionales que disponibilizan el acceso a los servicios y recursos pedagógicos y de accesibilidades en las escuelas de la red regular de enseñanza. Para ello, es necesario que las escuelas permitan un espacio adecuado para su instalación, así como un profesor especializado para AEE. El presente estudio tuvo como objetivo general caracterizar la actuación docente en salas de recursos multifuncionales (SRM) de escuelas de la red municipal de enseñanza de Macapá. Como objetivos específicos se pretendió: a) identificar al público que recibe atención educativa especializada en las SRMs; b) conocer las condiciones de funcionamiento y encaminamientos de alumnos para las SRM; c) identificar cómo el profesor organiza su trabajo docente, y d) verificar lo que los profesores piensan sobre la inclusión escolar e implicaciones en la actuación docente. Consistió en una investigación de carácter cualitativo con cuño exploratorio-descriptivo y fue realizada en Escuelas de la red pública municipal de enseñanza en Macapá; con una participación de seis (6) profesores que actuaban en el Servicio Educativo Especializado. Escuelas donde los maestros entrevistados estaban trabajando estaban ubicados en diferentes zonas de la ciudad de Macapá, distribuido entre el Norte, Sur, Este y Oeste, por un total de dos (2) escuelas en el sur, dos (2) en el norte, un (1 ) y la zona occidental (1) en el este. La recolección de datos se dio por medio de la aplicación de entrevista a los profesores que fueron seleccionados a través de sorteo. Los datos analizados fueron organizados en ejes temáticos con base en las informaciones obtenidas en las entrevistas. Los resultados revelaron que los profesores de la AEE tienen una concepción positiva sobre la inclusión. Se verificó que una parte de las salas de recursos multifuncionales no dispone de todos los recursos necesarios para la atención de los alumnos, y cuando tienen recursos como juegos, equipos y computadoras, los mismos no funcionan. El encaminamiento de los alumnos para la atención educativa especializada es hecho por la secretaría de la escuela y en algunas situaciones la Secretaría Municipal de Educación, a través de la División de Enseñanza Especial, realiza ese encaminamiento. Los participantes señalaron que la planificación de la atención de los alumnos se realiza, en su mayoría en asociación con los profesores de la sala de clase regular. Como resultado se observó también que los profesores atienden a una clientela bastante diversificada, lo que exige una formación adecuada que contemple las demandas exigidas por el proceso de inclusión escolar y que propicien el aprendizaje de los alumnos, lo que requiere una propuesta del sector público, a la formación continuada para estos profesionales. Los datos evidenciaron la importancia del apoyo de las familias, de los órganos responsables de la educación especial y de la escuela en su conjunto. Se espera que esta investigación pueda contribuir con el conocimiento científico y que incentive futuros trabajos que vengan a discutir sobre la Educación Especial en el municipio de Macapá.
Teaching performance in the room of multifunctional resources of the municipal network of Macapá / AP
Actuación docente en la sala de recursos multifuncionales de la red municipal de Macapá / AP
Keywords: Educação especial; Atuação docente; Sala de recursos multifuncional; Special education; Teaching performance; Multifunctional resource room; Educación especial; Actuación docente; Sala de recursos multifunción; CIENCIAS HUMANAS::EDUCACAO